Population Density Analysis on the Availability of Residential Space in Taubneno Village and Kota Baru Village, Kota Soe District, South Central Timor Regency - Maria Petronela Jois Teifa; Mikael Samin; Muhammad Husain Hasan (Socio-Economic and Humanistic Aspects for Township and Industry, 2026)
The increasing population growth in urban areas has caused problems related to limited residential space. This study aims to analyze the relationship between population density and building density on the availability of residential space in Taubneno Village and Kota Baru Village, Kota Soe District, South Central Timor Regency. This study uses a descriptive method with a quantitative approach through Normalized Difference Built-up Index (NDBI) analysis. Data were obtained through literature studies, Population data collection, remote sensing (Sentinel Imagery and Soe City administrative boundaries), observation, and documentation. Data analysis was carried out to determine the category of population density and building density in each village. The results of the study show that the population density in both villages is classified as High, with Taubneno Village having a larger population, compared to Kota Baru Village. Based on the results of the NBDI analysis, most areas of Taubneno Village are dominated by dense buildings, while Kota Baru Village shows an uneven pattern of building distribution, with dense areas in the center of the Village and sparse areas on the outskirts. These findings indicate a strong relationship between population density and building density, with higher population densities contributing to higher building density. The results of this study are expected to inform sustainable spatial planning in Kota Soe District, South Central Timor Regency.